PENGARUH PROMOSI JABATAN, PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Saputra, I Dw Gd Agus; Sudharma, I Nyoman (E-Jurnal Manajemen, 2017)
Good human resources are in need of good management in an organization, if in an organization are low job satisfaction, it will cause more and more complaints from the complaints of the employees. This study was conducted to determine how the effect of promotion, training and work environment on employee job satisfaction. This research was conducted at Bali Zoo employees. The data collection is done by distributing questionnaires using 5-point Likert scale to measure 14 indicators while data analysis techniques in this study using multiple linear regression. The results of data analysis showed promotions positive and significant effect on employee job satisfaction, training and significant positive effect on employee job satisfaction and work environment positive and significant effect on employee job satisfaction. Limitations of this study is the only research discusses some of the variables that affect job satisfaction, so that research results can only explain how the effect of promotion, training and work environment only.
Keywords: promotion, training, work environment, job satisfaction